Bond behavior evaluation of deformed rebar dependent on lateral pressure confinement including various structural parameters. (May 2021) - Farooq, Usman; Nakamura, Hikaru; Miura, Taito
Abstract: An analytical method based on Three-Dimensional Rigid Body Spring Model (3D RBSM) was proposed to evaluate the bond behavior of deformed rebar in RC structures dependent on lateral pressure confinement conditions. The method used voronoi mesh and beam element to model concrete and reinforcement respectively that was previously proposed by authors to simulate split failure only. In this study, applicability was extended to evaluate transition from split to pullout failure by extending proposed local bond model. It was confirmed that this simple beam element-based model can reproduce experimentally observed bond behavior dependent on various lateral pressure levels and frictional conditions. Most importantly, method can evaluate the internal cracking and stress distribution governed failure mechanisms dependent on confinement conditions. Meanwhile, in comparison to FEM and RBSM based models with 3D formation of rebar with rib, the proposed model is an efficient and economical alternative to evaluate confinement effects in RC members. Highlights: A beam element based 3D RBSM method is used to evaluate bond behavior. It realistically simulates transition from split to the pullout failure mode. The method evaluates bond dependency on pressure in combination of friction and cover. The failure mechanism is governed based on internal crack and stress propagation. The method is an efficient and economical tool to evaluate bond performance.